Concern about food safety - Cherednichenko, Galina (My University, 2014)
We all must learn about safe food handling. While many people assume that foodborne illness is contracted primarily in restaurants, it is revealing to discover that each of us is his or her own worst enemy. Food properly handled in home kitchens would reduce the incidence of disease dramatically. Labels and leaflets with safe food handling instructions can be found on or near fresh meat and poultry and are part of the effort to empower the consumer to handle these products safely.
Keywords: безопасность; пищевые продукты; забота; safety; care; food; безпека; харчові продукти; турбота; кафедра ділової іноземної мови та міжнародної комунікації